Identification of novel QTLs and development of KASP markers for sugar content in fresh and dried peanut (Arachis hypogaea L.) - Zhang, Chi; Liu, Mingshuo; Cui, Shunli; Chen, Miao; Deng, Hongtao; Liu, Lifeng; Liu, Yingru; Li, Xiukun; Chen, Xiaoshu; Hou, Mingyu (Frontiers in Plant Science, 2026)
The total sugar content (TSC), soluble sugar content (SSC), and sucrose content (SC) are key determinants of taste and flavor of fresh and dried peanut kernels, and are important quality indicators in peanut breeding. However, the quantitative trait locus (QTLs) regulating peanut sugar content, especially in fresh seeds, remain poorly understood. In this study, TSC, SSC, and SC were measured in dried mature seeds (DMS) across four environments (three-year data from Baoding and Fuxin) and in fresh seeds (FS) across two environments (Baoding and Fuxin), and QTL mapping was performed in a recombinant inbred line (RIL) population (‘Silihong’×’Jinonghei3’). TSC, SSC, and SC were all lower in FS compared to DMS, indicating that the sugar content increased during the drying and maturation process. Two major co-localized QTLs, qA06 (physical location 115.08-115.73 Mb) and qB06 (physical location 147.74-148.46 Mb), were identified in multiple environments. qA06 was associated with TSC, SSC, and SC in DMS, and SSC in FS, spanning a 0.65 Mb physical interval. qB06, spanning a 0.72Mb physical interval, was associated with TSC, SSC, SC in DMS, and TSC, SSC in FS. qB06 represents a newly identified QTL in this study; within 56 candidate genes and 319 SNPs were screened. Among them, the genes arahy.3URM83 and arahy.41Y8R9, and arahy.P7PTW7 were closely related to sugar synthesis. Transcriptome analysis during the drying and maturation stages revealed that arahy.3URM83 and arahy.41Y8R9 were strongly associated with sugar content. The QTL regions identified in this study not only elucidate the genetic regulatory mechanism of peanut sugar content under different drying conditions but also enable the development of KASP markers, offering valuable resources for peanut quality improvement and targeted breeding programs.